Subacute sarcoid myositis with ocular muscle involvement; a case report and review of the literature - Hayashi, Y; Ishii, Yoshiki; Nagasawa, J.; Arai, S.; Okada, H.; Ohmi, F.; Umetsu, T.; Machida, Y.; Kurasawa, K.; Takemasa, A.; Suzuki, S.; Senoh, T.; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Sarcoidosis is a chronic granulomatous disease that can affect multiple organs. The lungs, eyes, and skin are known to be highly affected organs in sarcoidosis. There have been reports based on random muscle biopsy that 32-80% of systemic sarcoidosis comprises noncaseating granulomas; however, muscle involvement in sarcoidosis is generally asymptomatic and has an unknown frequency. We describe a case of acute to subacute sarcoid myositis of the skeletal and extraocular muscles. Typical ophthalmic involvement (manifested by infiltration of the ocular adnexa, intraocular inflammation, or infiltration of the retrobulbar visual pathways) and extraocular sarcoid myositis (as with the present case) is infrequently reported. It is important to keep in mind the rare yet perhaps underestimated entity of sarcoid myositis, and to utilize muscle biopsy and imaging tests for appropriate diagnosis and management of patients with sarcoidosis.